Nutrição cálcica e potássica em quiabeiro irrigado com água salina em ambiente protegido - Costa, Jessilanne Plínia Barbosa de Medeiros (Universidade Federal Rural do Semi-Árido, 2019)
The okra (Abelmoschus esculentus L.) is a culture sensitive to salinity. For a good development of the plant when using saline water a strategy must be adopted in order to inhibit saline stress. In view of the above, two experiments (I and II) were developed with the aim of evaluating calcium (I) and potassium (II) supplementation in order to reduce the effect of salinity. The experiments were conducted in a greenhouse at the Federal Rural University of Semi-Arid, in Mossoró. The experimental design used for the two experiments was completely randomized, in a 2 x 5 factorial scheme, with 4 replications. In experiment I, two okra cultivars (Santa Cruz 47 and Valença) were used fertigated with 5 nutrient solutions: F1 - SNP standard nutrient solution (CEa = 0.5 dS m-1); F2 - SNP + NaCl (CEa = 3.5 dS m-1); F3 - SNP + NaCl (CEa = 3.5 dS m-1) + extra addition in 50% Ca; F4 - SNP + NaCl (CEa = 3.5 dS m-1) + extra addition in 100% Ca; F5 - SNP + NaCl (CEa = 3.5 dS m-1) + extra addition at 150% Ca. In experiment II, the same fertigated cultivars 5 nutrient solutions: F1 - Standard nutrient solution, SNP (CEa = 0.5 dS m-1); F2 - SNP + NaCl (CEa = 3.5 dS m-1); F3 - SNP + NaCl (CEa = 3.5 dS m-1) + extra addition in 50% K; F4 - SNP + NaCl (CEa = 3.5 dS m-1) + extra addition in 100% K; F5 - SNP + NaCl (CEa = 3.5 dS m-1) + extra addition in 150% of K. The variables analyzed were: development (height, number of leaves, stem diameter, leaf area) dry phytomass of (leaves, stem, fruits and total); yield (number of fruits, fruit length, fruit diameter and yield) and post-harvest quality (hydrogen potential, titratable acidity, soluble solids and SS/AT ratio). Fertigation did not influence growth, yield and quality characteristics, however, potassium supplementation provided an increase in dry plant phytomass for cv. Santa Cruz 47 and reduction for cv. Valença. The cultivars used did not suffer salt stress due to the frequency of irrigation adopted. Salinity increased the SS/AT ratio in experiment I for cv. Santa Cruz 47
Keywords: Abelmoschus esculentus L.; Estresse salino; Nutrição mineral; Abelmoschus esculentus L.; Salt stress; Mineral nutrition; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO